A Study On the Effectiveness of Rolling Barrier System at Straight Road and Curved Road: A Review - Shaffie, Ekarizan; Mohd Zin, Nursafa Maisara; Shiong, Fionna; Arshad, Ahmad Kamil; Ahmad, Juraidah (International Journal of Integrated Engineering, 2023)
The rolling barrier system is part of the road safety infrastructure that is used to improve and maintain road safety. It is also possible to overcome and reduce the number of crashes. A rolling barrier is a type of safety device that not only absorbs but also converts shock energy into rotational energy, thereby preventing fatal accidents for drivers and passengers. A rolling barrier should be installed in areas where vehicles are frequently collided. By absorbing shock energy, a rolling barrier will safely guide a vehicle back to the road or stopped the vehicle. This study was built on the findings of a previous study to determine the effectiveness of a rolling barrier system for use on both straight and curved roads. This research focuses on a new invention, the rolling barrier system, as opposed to the traditional barrier, in order to learn more about its mechanism and function. The study’s scope was limited to focusing on the implementation of the rolling barrier system on straight and curved roads. According to the previous study, straight and curved roads have the highest incident rates compared to other types of roads. The Rolling Barrier System was strategically installed in three high-risk areas with a high incidence of fatal traffic incidents. The three high-risk road locations that require additional safety are straight roads, curving roads, and hilly roads, which are the most important locations to place Rolling Barrier Systems in order to decrease high-risk accidents and fatalities while also improving road safety. There are four types of roads that are appropriate for implementing a Rolling Barrier System. The Rolling Barrier types are straight roadside Rolling Barriers, curved roadside Rolling Barriers, steep roadside Rolling Barriers, and median Rolling Barriers.